Agile or waterfall development: The Clementon Company dilemma. Issue 1 (1st May 2022) - Chandran, Karthikeyan; Das Aundhe, Madhuchhanda
This case study documents the challenges faced by Iota Consultancy Services, an IT Service organization, as it simultaneously developed and deployed an IT Services Management software product for one of its premier clients, The Clementon Company. A leading market research firm, The Clementon Company had its footprints across the globe. Its recent acquisition of several smaller research agencies had created a complex IT landscape, in terms of the technologies adopted and the processes followed. In Iota Consultancy Services' 10-year-old history, this engagement with The Clementon Company was a significant milestone, consisting of two parts—(1) Streamlining and standardizing The Clementon Company's IT processes and (2) maintaining The Clementon Company's organization-wide IT infrastructure. Iota Consultancy Services began this crucial assignment with an initial study to identify a product for the The Clementon Company's IT department. Iota Consultancy Services, a rapidly growing player in the sector, had indigenously developed a few IT products, as well. It had an IT Services Management product called Helpdesk Management. Being the sole service provider for maintaining The Clementon Company's entire IT infrastructure, Iota Consultancy Services felt that Helpdesk Management could be deployed as a single tool across the organization. However, until now, Helpdesk Management had never been deployed as a comprehensive IT Services Management product for any organization. This meant that Iota Consultancy Services needed to simultaneously enhance its Helpdesk Management tool by developing new features, and also deploy it for The Clementon Company. This was Iota Consultancy Services' chance to earn a reputation as a successful product company, which would result in increased revenue. However, if things did not go well, Iota Consultancy Services could lose face forever. Iota Consultancy Services' dilemma was whether it should propose Helpdesk Management as a tool for The Clementon Company, or not. At this juncture, everything depended on whether Iota Consultancy Services could successfully customize the Helpdesk Management tool to suit The Clementon Company's requirements.